The hydrogeology and hydrogeochemisty of the aquifers of the Hex River Valley, Cape Province - Rosewarne, Peter Nigel (Rhodes University, Faculty of Science, Department of Geography, 1984)
The Hex River Valley is one of the main centres in South Africa for cultivation of table grapes of export quality. The vines require irrigation water, which must be low in dissolved solids. Approximately two thirds of the annual irrigation requirement is obtained from boreholes and the balance from surface water sources. During the early 1960s a deterioration in the quality of the groundwater was noticed, becoming critical in some areas, and borehole yields also declined. The main objectives of this study were therefore to obtain an understanding of the hydrogeological and hydrogeochemical processes operating in the valley to explain the derogation of the groundwater resource and enable optimum utilisation and management of the resource in the future. To achieve these objectives, field work involving exploration drilling, aquifer tests, hydrocensus, long-term monitoring of groundwater levels and surfacewater flows and extensive sampling of the ground and surface waters was carried out. Analysis of these data gave quantitative information on groundwater occurrence, aquifer hydraulic properties, groundwater recharge and storage, chemical characteristics of the ground and surfacewaters and sources of dissolved species.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Hydrogeology; Aquifers; Water chemistry; Hydrogeology -- South Africa -- Cape Colony